Repeat Dynamics across Timescales: A Perspective from Sibling Allotetraploid Marsh Orchids (Dactylorhiza majalis s.l.) - Eriksson, Mimmi C; Mandáková, Terezie; McCann, Jamie; Temsch, Eva M; Chase, Mark W; Hedrén, Mikael; Weiss-Schneeweiss, Hanna; Paun, Ovidiu (Molecular biology and evolution, 2022)
To provide insights into the fate of transposable elements (TEs) across timescales in a post-polyploidization context, we comparatively investigate five sibling Dactylorhiza allotetraploids (Orchidaceae) formed independently and sequentially between 500 and 100K generations ago by unidirectional hybridization between diploids D. fuchsii and D. incarnata. Our results first reveal that the paternal D. incarnata genome shows a marked increased content of LTR retrotransposons compared to the maternal species, reflected in its larger genome size and consistent with a previously hypothesized bottleneck. With regard to the allopolyploids, in the youngest D. purpurella both genome size and TE composition appear to be largely additive with respect to parents, whereas for polyploids of intermediate ages we uncover rampant genome expansion on a magnitude of multiple entire genomes of some plants such as Arabidopsis. The oldest allopolyploids in the series are not larger than the intermediate ones. A putative tandem repeat, potentially derived from a non-autonomous miniature inverted-repeat TE (MITE) drives much of the genome dynamics in the allopolyploids. The highly dynamic MITE-like element is found in higher proportions in the maternal diploid, D. fuchsii, but is observed to increase in copy number in both subgenomes of the allopolyploids. Altogether, the fate of repeats appears strongly regulated and therefore predictable across multiple independent allopolyploidization events in this system. Apart from the MITE-like element, we consistently document a mild genomic shock following the allopolyploidizations investigated here, which may be linked to their relatively large genome sizes, possibly associated with strong selection against further genome expansions.
Keywords: mokřady; Genome, Plant; genom rostlinný; marsh orchids; Orchidaceae; Siblings; transposable elements; transpozibilní elementy DNA; Wetlands; allopolyploidy; DNA Transposable Elements; lidé; Humans; Diploidy; genome size; sourozenci; Polyploidy; genomic shock; diploidie; polyploidie